Concerns about strenght tests in gymnastics: a systematic review - Gasparetto, Z.; Julião, A. L.; Thuany, M.; Martinez, P. F.; de Mendonça Bacciotti, S.; de Oliveira-Junior, S. A. (Science of Gymnastics Journal, 2022)
This study aims to analyze the specialized literature on the protocols, instruments, and techniques used to train and assess strength in gymnastics practitioners or athletes who are represented by the International Gymnastics Federation (Fédération Internationale de Gymnastique - FIG). The systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Systematic searches on the PubMed, Web of Science, Scopus, LILACS, SciELO, and SPORTDiscus databases were conducted using the following keywords: "assessment," OR "measurement," OR "evaluation," AND "child*," OR "young," OR "adolesc*," AND "athlete*," OR "practitioner," OR "gymnast*," AND "gymnastic*," OR "trampoline," AND "muscle strength," OR "muscle power," OR "strength," OR "power," OR "concentric," OR "performance," OR "explosive strength," OR "motor tests". Studies included in this review address the assessment and training of strength in gymnastics or athletes. Fourteen studies assessing the physical capacity strength in practitioners or gymnastic athletes were the basis of this systematic review. These articles describe low-cost, easy-to-apply protocols and instruments performed in the training gym. The included articles focused on assessing the strength level of adolescent male and female practitioners or athletes for talent selection and detection, as well as lesion reduction. Despite the benefits of strength training, such as better performance and fewer injuries, in general, strength is not regularly assessed. Only studies encompassing artistic and rhythmic gymnastics were found.